2015
DOI: 10.3322/caac.21287
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cancer prevention: Current status and future directions

Abstract: The heterogeneity and complexity of advanced cancers strongly supports the rationale for an enhanced focus on molecular prevention as a priority strategy to reduce the burden of cancer. Molecular prevention encompasses traditional chemopreventive agents as well as vaccinations and therapeutic approaches to cancer-predisposing conditions. Despite challenges to the field, we now have refined insights into cancer etiology and early pathogenesis; successful risk assessment and new risk models; agents with broad pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 297 publications
(274 reference statements)
1
67
0
2
Order By: Relevance
“…Genetic background and environmental and dietary factors have a role in breast cancer development. In the normal breast tissue, there is a balance between negative and positive growth factors, so to develop, breast cancer requires loss or gain in some functions [5]. The following factors are thought to be related to breast cancer development:…”
Section: Breast Cancer Risk Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Genetic background and environmental and dietary factors have a role in breast cancer development. In the normal breast tissue, there is a balance between negative and positive growth factors, so to develop, breast cancer requires loss or gain in some functions [5]. The following factors are thought to be related to breast cancer development:…”
Section: Breast Cancer Risk Factorsmentioning
confidence: 99%
“…Recently, it has been suggested that overexpression of oestrogen receptors in the normal breast epithelium increases breast cancer risk in women [5].…”
Section: Hormonal Statusmentioning
confidence: 99%
See 3 more Smart Citations